176k views
4 votes
Determine the next step for solving the quadratic equation by completing the square.

0 = –2x2 + 2x + 3
–3 = –2x2 + 2x
–3 = –2(x2 – x)
–3 + = –2(x2 – x + )
StartFraction negative 7 Over 2 EndFraction = –2(x – StartFraction 1 Over 2 EndFraction)2
StartFraction 7 Over 4 EndFraction = (x – StartFraction 1 Over 2 EndFraction)2
The two solutions are Plus or minus StartFraction StartRoot 7 EndRoot Over 2 EndFraction

2 Answers

4 votes

Answer:

A) StartFraction negative 7 Over 2 EndFraction = –2(x – StartFraction 1 Over 2 EndFraction)2

Explanation:

–3 + = –2(x² – x + )

-3 + -2(½)² = -2(x² - 2(x)(½) + (½)²)

-3 - ½ = -2(x - ½)²

-7/2 = -2(x - ½)²

User Nikratio
by
5.2k points
1 vote

Answer:

-7/2 = -2(x-1/2)^2

Explanation:

0 = –2x^2 + 2x + 3

Subtract 3 from each side

-3 = –2x^2 + 2x

Factor out the -2

-3 =- 2(x^2 -x)

Take the coefficient of x and divide by 2 and square it

-1 /2 = -1/2 ^2 = 1/4

Add it to each side Remember the -2 on the outside so we need to multiply it by -2

-2 *1/4 = -1/2

-3 -1/2= -2(x^2 -x +1/4)

-7/2 = -2(x^2 -x +1/4)

-7/2 = -2(x-1/2)^2

User Muizz Mahdy
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.